2021
DOI: 10.1039/d1ra03957a
|View full text |Cite
|
Sign up to set email alerts
|

Terpyridine-derived perovskite single crystals with tunable structures and electronic dimensionality

Abstract: Terpyridine-derived perovskite single crystals displaying tunable low-dimensional structures and outstanding optoelectronic performances suitable for device applications have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…The formation of organic‐inorganic octahedra is attributed to the stronger chemical binding of K + to F − comparison to Br − . Similar organic‐organic octahedra formation was seen in (C 15 H 10 N 6 ) 4 Pb 5 I 18 , where part of the Pb−I bonds in [PbI 6 ] 4− octahedron were replaced by Pb−N bonds [8] …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The formation of organic‐inorganic octahedra is attributed to the stronger chemical binding of K + to F − comparison to Br − . Similar organic‐organic octahedra formation was seen in (C 15 H 10 N 6 ) 4 Pb 5 I 18 , where part of the Pb−I bonds in [PbI 6 ] 4− octahedron were replaced by Pb−N bonds [8] …”
Section: Resultsmentioning
confidence: 55%
“…Similar organic-organic octahedra formation was seen in (C 15 H 10 N 6 ) 4 Pb 5 I 18 , where part of the PbÀ I bonds in [PbI 6 ] 4À octahedron were replaced by PbÀ N bonds. [8] To confirm the interaction between F atom in DFPD + and K + , we measured the binding energy of F atom in (DFPD) 2 KInBr 6 by X-ray photoelectron spectroscopy (XPS). It is found that F1s XPS spectrum of the (DFPD) 2 KInBr 6 crystals has shifted by about 0.32 eV towards lower binding energy with respect to the DFPD-Br precursor (Figure 1c, Figure S2), indicating a different chemical environment from that of DFPD-Br and the presence of an additional interaction of F with K + .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, we calculate that the bandgaps of Tpy 4 Pb 5 I 18 and Tpy 2 Pb 3 I 6 are 1.58 eV and 1.57 eV, respectively. [ 61 ] Gassara et al. synthesized 1D perovskite, (C 6 H 7 NBr) 3 [CdBr 5 ], and calculated DFT, and obtained that the indirect bandgap of the perovskite is 3.16 eV.…”
Section: Electronic Structures Of Ld Perovskitesmentioning
confidence: 99%
“…It is found that with an increase in the alkyl chain length, the phase distribution of 2D perovskite crystals becomes disordered and the orientation decreases . A series of new perovskite single crystals has been grown by Yuan et al, 0D Tpy 2 PbI 6 , 1D Tpy 4 Pb 5 I 18 , and 1D Tpy 2 Pb 3 I 6 , derived from terpyridine by regulating the proportion of the components . Xing et al.…”
Section: Introductionmentioning
confidence: 99%
“…23 A series of new perovskite single crystals has been grown by Yuan et al, 0D Tpy 2 PbI 6 , 1D Tpy 4 Pb 5 I 18 , and 1D Tpy 2 Pb 3 I 6 , derived from terpyridine by regulating the proportion of the components. 24 Xing et al used a large volume of 2-(methylthio) ethylamine hydrochloride (MTEACl) to prepare a low-dimensional perovskite layer. Owing to the S−S interaction between sulfur atoms of MTEA molecules, the charge transport and stability of the perovskite framework have been enhanced.…”
Section: ■ Introductionmentioning
confidence: 99%